Analysis of Intra-Industry Trade in Cosmetic Commodities between Indonesia and Nine Trading Partners in The Asian Region in 2004-2018 Period - Ramadhan, Tuhfah Ikbar; Firmansyah, Firmansyah (AFEBI Economic and Finance Review, 2020)
This research aims to analyze the level of intra-industry trade and the effect of average country size, average per capita income, difference in per capita income, distance, and average tariff on intra-industry trade of cosmetic commodities between Indonesia and nine trading partners (Singapore, Malaysia, Thailand, Philippines, India, China, Hong Kong, Japan, and South Korea) from 2004-2018. This study uses a Grubel-Llyod Index to determine the level of intra-industry trade and static panel data method to see the effect of independent variables on the level of intra-industry trade. The result shows that the level of intra-industry trade of cosmetic commodities between Indonesia and its trading partners (except India) still tended to be low. The average country size, average per capita income, and average tariff have a positive and significant effect on the level of intra-industry trade. Meanwhile, the difference in per capita income and distance have a negative and significant effect.